THE EFFECT OF THE BARBIE DOLL MEDIA TOWARD SELF-CARE ABILITY FOR STUDENT WITH MILD INTELLECTUAL DISABILITY - Ningsih, Arista Surya; Huda, Abdul (Department of Special Education, 2016)
The purpose of this research was to analyze the effect of barbie doll media toward self care ability for student with mild intellectual disability in the first grade. This study used a Single Subject Research (SSR) with the A-B-A design model. The subject was SE (10 years), a student with mild intellectual disability in the first grade. Based on the data processing, the mean level of baseline condition-1 was 57,25%, the mean level in the intervention condition was 91,93%, the mean levels in the baseline condition-2 was79,3%. The conclusion of this research was there is a effect of Barbie doll media toward the ability of clothe self care for student of mild intellectual disability. The advice given is the teachers can a provide method and media appropriate learning and accommodate student in processing information and optimizing the ability of the student.